### #1 - Complete The Equation

How can you make the following equation true by drawing only one straight line: 5+5+5=550 ?

Draw a line on the first plus sign. This turns it into a 4! The equation then becomes true: 545+5=550.

How can you make the following equation true by drawing only one straight line: 5+5+5=550 ?

1 dollar = 100 cent

= 10 cent x 10 cent

= 1/10 dollar x 1/10 dollar

= 1/100 dollar

= 1 cent

=> 1 dollar = 1 cent

solve this tricky problem ?

step 3 is wrong

0 0 0 = 6

1 1 1 = 6

2 2 2 = 6

3 3 3 = 6

4 4 4 = 6

5 5 5 = 6

6 6 6 = 6

7 7 7 = 6

8 8 8 = 6

9 9 9 = 6

You can use any mathematical symbols in the space provided to make all above algebraic expressions true.

(0! + 0! + 0! )! =6

(1! + 1! + 1! )! =6

2 + 2 + 2 = 6

3 * 3 - 3 = 6

4 + 4 -sqrt(4) = 6

5 + 5 / 5 = 6

6 + 6 - 6 = 6

7 - 7 / 7 =6

8 - sqrt(sqrt(8+8) = 6

(9 + 9) / sqrt(9) = 6

using four eights (8) and a one (1) and one mathematical symbol , create the number 100

188 - 88

Can you arrange four 9's and use of atmost 2 math symbols , make the total be 100?

99 / .99

I know there are two methods by using three time the same number with an plus(+) operator , you can make sum as 60.

One of them is 20+20+20.

whats the other way ?

The Other way is 55+5

Find the value of a by solving the maths equation in the picture below

2(remember bodmas)

Solve the maths equation in the picture below by placing the numbers 1 through 9 into the boxes so that all the 3 equations are correct.

There are six unique answers

Ans1:

7 x 4 = 28

36 / 4 = 9

1 + 4 = 5

Ans2:

9 x 4 = 36

28 / 4 = 7

1 + 4 = 5

Ans3:

3 x 8 = 24

56 / 8 = 7

1 + 8 = 9

Ans4:

7 x 8 = 56

24 / 8 = 3

1 + 8 = 9

Ans5:

4 x 8 = 32

56 / 8 = 7

1 + 8 = 9

Ans6:

7 x 8 = 56

32 / 8 = 4

1 + 8 = 9

We have arranged an array of numbers below. What you have to do is use any kind of mathematical symbol you know excluding any symbol that contains a number like cube root. You can use any amount of symbols but you have to come up with a valid equation for all of them.

0 0 0 = 6

1 1 1 = 6

2 + 2 + 2 = 6

3 3 3 = 6

4 4 4 = 6

5 5 5 = 6

6 6 6 = 6

7 7 7 = 6

8 8 8 = 6

9 9 9 = 6

(0! + 0! + 0!)! = 6

(1 + 1 + 1)! = 6

2 + 2 + 2 = 6

3 x 3 - 3 = 6

√4 + √4 + √4 = 6

5 + 5/5 = 6

6 + 6 - 6 = 6

7 - 7/7 = 6

8 - √√(8 + 8) = 6

√(9 x 9) - √9 = 6